2016
DOI: 10.4103/0970-1591.179191
|View full text |Cite
|
Sign up to set email alerts
|

Is surgeon intuition equivalent to models of operative complexity in determining the surgical approach for nephron sparing surgery?

Abstract: Introduction:The choice of approach for partial nephrectomy often depends on surgical complexity. We aimed to determine if surgeon intuition was equivalent to markers of operative complexity, such as RENAL nephrometry and Mayo adhesive probability (MAP) score, in determining the surgical approach for partial nephrectomy (PN).Materials and Methods:We retrospectively identified 119 masses removed for suspected renal cell carcinoma from January 2012 to September 2014 by a single surgeon who intuitively chose trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 22 publications
0
20
0
2
Order By: Relevance
“…Previous literature had suggested that patients with more complex renal masses were more likely to have an open PN [36]. Sharma et al [52] found that patients with a higher RENAL score were more likely to undergo an open procedure as well. On the contrary, the presence of adhesive perinephric fat did not influence the decision making.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous literature had suggested that patients with more complex renal masses were more likely to have an open PN [36]. Sharma et al [52] found that patients with a higher RENAL score were more likely to undergo an open procedure as well. On the contrary, the presence of adhesive perinephric fat did not influence the decision making.…”
Section: Discussionmentioning
confidence: 99%
“…The DAP score (p = 0.018) [49] and PASS (p = 0.02) [18] were independent predictors of renal function variation. PADUA (p = 0.05) [52] and RAIV (p = 0.052) [18] demonstrated a sort of correlation with renal function variation but they did not achieved the usual levels of statistical significance. (Table 2 and Fig.…”
Section: Postoperative Renal Functionmentioning
confidence: 92%
See 2 more Smart Citations
“…Анализ результатов исследований ряда авторов свидетельствует о наличии статистически значимой взаимосвязи между нефрометрическими данными и объемом хирургического вмешательства. При этом, помимо общей суммы, в роли отдельных предикторов выступают различные переменные и их сочетания [20,[28][29][30][31]. Также имеются немногочисленные данные о связи нефрометрических параметров с выбором методики хирургического вмешательства.…”
Section: A б вunclassified